Cyto‐histo correlation and false‐negative urine: Before and after the Paris system for reporting urinary cytology. Issue 8 (2nd June 2022) - Yuan, Lisi; Gero, Margaret; Zia, Shereen; Aryal, Sameer Chhetri; Shetty, Sindhu; Reynolds, Jordan P.
Abstract: Background: The impact of implementing the Paris system (TPS) on the rate of discrepant cases in the negative for high‐grade urothelial carcinoma (NHGUC) category that had a subsequent diagnosis of high‐grade urothelial carcinoma (HGUC) on histology is not well studied. Methods: We adopted TPS in May 2019. We searched discrepant cases with negative urine cytology 2017–2019 in our cyto‐histo correlation database. The urine cytology and follow‐up biopsy/resection were reviewed by a cytopathologist who also did Genitourinary (GU) Pathology subspecialty sign‐out. Voided urine and instrumented urine were included in this study. Results: There were total of 70 discrepant cases with negative cytology interpretation but HGUC on the subsequent biopsy or resected specimen. Following the TPS criteria, the rate of discrepant negative cytology cases increased from 6 cases between January 2017 and May 2019 to 64 cases after May 2019 when we adopted TPS. There were 2 discrepant negative cases in 2017, 3 cases in 2018, and 65 cases in 2019. Out of 65 cases in 2019, 64 cases were identified after May 2019. Additional 55 urine cytology slides were reviewed according to the TPS criteria, of which, the diagnoses remained unchanged in 45 (82%) cases and 10 (19%) cases were reassigned to either atypical or suspicious categories. The discrepancy was noted more on the instrumented urine and the upper tract urine. However, the false‐negative rate rose faster in voided urine and lower tract urine. The risk of HGUC with the category of NHGUC was 0.03% in 2017, 0.05% in 2018, and 1.06% in 2019 at our institution. The increase in false‐negative rate could not be attributed to a single cytopathologist. Conclusion: After adopting TPS for reporting urine cytology, there was an increase in HGUC from negative urine cytology which was subsequently confirmed on histology as cases of HGUC. The quality control of negative urines could be important monitoring the process when implementing TPS.